2019
DOI: 10.1111/jam.14304
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota of newborn piglets with intrauterine growth restriction have lower diversity and different taxonomic abundances

Abstract: Aim Intrauterine growth retardation (IUGR) is a prevalent problem in mammals. The present study was conducted to unveil the alterations in intestinal microbiota in IUGR piglets. Methods and Results We identified the alterations of small intestinal microbiota in IUGR piglets on 7, 21 and 28 days of age using 16S rRNA sequencing. The results showed that IUGR piglets had a decreased alpha diversity of jejunum microbiota at 7 and 21 days of age; had lower abundances of Bacteroidetes and Bacteroides in the jejunum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
70
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 67 publications
11
70
1
Order By: Relevance
“…Interestingly, when compared to NBW pigs, IUGR pigs showed lower expression of genes involved in lipid metabolism, glyoxylate and dicarboxylate metabolism, amino acid metabolism, energy metabolism, terpenoid and polyketide metabolism, xenobiotic biodegradation and metabolism, cofactor metabolism, and vitamin metabolism, consistent with the results of our previous study [14]. The downregulation of amino acid metabolism is consistent with lower concentrations of most amino acids observed in IUGR pigs [47].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, when compared to NBW pigs, IUGR pigs showed lower expression of genes involved in lipid metabolism, glyoxylate and dicarboxylate metabolism, amino acid metabolism, energy metabolism, terpenoid and polyketide metabolism, xenobiotic biodegradation and metabolism, cofactor metabolism, and vitamin metabolism, consistent with the results of our previous study [14]. The downregulation of amino acid metabolism is consistent with lower concentrations of most amino acids observed in IUGR pigs [47].…”
Section: Discussionsupporting
confidence: 90%
“…In a previous study, we reported alterations in the microbial communities of the small intestine in IUGR piglets at 7, 21, and 28 d of age, and that Bacteroidetes, Bacteroides, Escherichia-Shigella, and Pasteurella could be related to nutrient digestion and absorption, and growth and development regulation [14]. Microbial communities in the intestine are influenced by various environmental factors, including age, diet, lifestyle, and medication [17].…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, microbiota establishment in LBW human infants, particularly those born prematurely, is different to that of NBW infants (Fança-Berthon et al, 2010;Unger et al, 2015) with similar effects reported in mice (Wang et al, 2016). Differences in the microbiota community composition have been identified in LBW pigs at different intestinal sites and in the faeces (Li et al, , 2019Huang et al, 2019;Zhang et al, 2019). In the present study, differences in microbiota diversity were noted preand post-weaning, although inconsistent longitudinally.…”
Section: Discussionsupporting
confidence: 41%
“…early life (D'Inca et al, 2010(D'Inca et al, , 2011. More recent studies have demonstrated the microbiota community composition of the jejunum, ileum, colon (Li et al, 2019;Zhang et al, 2019) and faeces to differ between LBW and NBW pigs up to 5 weeks of age. Whilst studies have identified microbiota characteristics related to growth of pre-weaned and weaned pigs (Mach et al, 2015;Ding et al, 2019), as well as feed efficiency of grower-finisher pigs (McCormack et al, 2017;Han et al, 2018;Quan et al, 2018), no published studies have compared the faecal microbiota of LBW piglets able to exhibit compensatory growth to those who remain stunted, in comparison to NBW pigs.…”
Section: Introductionmentioning
confidence: 99%
“…The relative abundance of gut microbiota at phyla and genera levels during pregnancy and lactation was analyzed via Metastats analysis ( http://metastats.cbcb.umd.edu/ ) [ 17 ]. Spearman's correlation between the fecal metabolites, plasma indexes, and relative abundance of different microbial genera was performed using the R package [ 18 ]. All data were presented as means ± standard error of mean (SEM) and considered statistically significant when P < 0.05.…”
Section: Methodsmentioning
confidence: 99%